Pediatric Inflammatory Bowel Disease with Cytoplasmic Staining of Antineutrophil Cytoplasmic Antibodies - Omar I. Saadah; Jamil A. Al-Mughales (Clinical and Developmental Immunology)
Background. It is unusual for the antineutrophil cytoplasmic antibody with cytoplasmic pattern (cANCA) to present in patients with inflammatory bowel disease (IBD) without vasculitis. The purpose of this study was to describe the occurrence and characteristics of pediatrics IBD with cANCA. Methods. A retrospective review of pediatric IBD associated with cANCA serology in patients from King Abdulaziz University Hospital, Saudi Arabia, between September 2002 and February 2012. Results. Out of 131 patients with IBD screened for cANCAs, cANCA was positive in 7 (5.3%) patients of whom 4 had ulcerative colitis and 3 had Crohn's disease. The median age was 8.8 years (2–14.8 years). Six (86%) were males. Of the 7 patients, 5 (71%) were Saudi Arabians and 2 were of Indian ethnicity. The most common symptoms were diarrhea, abdominal pain, weight loss, and rectal bleeding. None had family history or clinical features suggestive of vasculitis involving renal and respiratory systems. No difference in the disease location or severity was observed between cANCA positive and cANCA negative patients apart from male preponderance in cANCA positive patients. Conclusion. The occurrence of cANCA in pediatric IBD is rare. Apart from male preponderance, there were no peculiar characteristics for the cANCA positive patients.